Information discernment and the psychophysiological effects of misinformation. Issue 8 (6th September 2021) - Walton, Geoff; Pointon, Matthew; Barker, Jamie; Turner, Martin; Wilkinson, Andrew Joseph
Abstract : Purpose: The purpose of this paper is to determine to what extent a person's psychophysiological well-being is affected by misinformation and whether their level of information discernment has any positive or negative effect on the outcome. Design/methodology/approach: Participants ( n = 48) were randomly and blindly allocated to one of two groups: control group participants were told a person they were working with was a student; experimental group participants were additionally led to believe that this other participant had extreme religious views. This was both stigmatising and misinforming, as this other person was an actor. Participants completed a pre-screening booklet and a series of tasks. Participants' cardiovascular responses were measured during the procedure. Findings: Participants with high levels of information discernment, i.e. those who are curious, use multiple sources to verify information, are sceptical about search engine information, are cognisant of the importance of authority and are aware that knowledge changes and is contradictory at times exhibited an adaptive stress response, i.e. healthy psychophysiological outcomes and responded with positive emotions before and after a stressful task. Social implications: The findings indicate the potential harmful effects of misinformation and discuss how information literacy or Metaliteracy interventions may address this issue. Originality/value: The first study to combine the hitherto unrelated theoretical areas of information discernment (a sub-set of information literacy), affective states (positive affect negative affect survey) and stress (challenge and threat cardiovascular measures).